New route to eremophilanes: synthesis of (+/-)-eremophilenolide, (+/-)-eremophiledinone, and (+/-)-deoxyeremopetasidione - Srinivas, P.; Reddy, D. Srinivasa; Kumar, K. Shiva; Dubey, P. K.; Iqbal, Javed; Das, Parthasarathi (Tetrahedron Letters, 2008)
A new and efficient route to the family of eremophilanes is reported. Key steps are the highly stereocontrolled Diels-Alder reaction and aldol condensation to furnish a cis-decalin system with the desired stereochemistry present in the eremophilane family of natural products. This approach is general and was utilized for the synthesis of (+/-)-eremophilenolide, (+/-)-eremophiledinone, and (+/-)-deoxyeremopetasidione. (C) 2008 Elsevier Ltd. All rights reserved.

Novel pyrazole-3-carboxamide derivatives as cannabinoid-1 (CB1) antagonists: journey from non-polar to polar amides - Sasmal, Pradip K.; Reddy, D. Srinivasa; Talwar, Rashmi; Venkatesham, B.; Balasubrahmanyam, D.; Kannan, M.; Srinivas, P.; Kumar, K. Shiva; Devi, B. Neelima; Jadhav, Vikram P.; Khan, Sanjoy K.; Mohan, Priya; et al. (Bioorganic & Medicinal Chemistry Letters, 2011)
The synthesis and biological evaluation of novel pyrazole-3-carboxamide derivatives as CB1 antagonists are described. As a part of eastern amide SAR, various chemically diverse motifs were introduced. In general, a range of modifications were well tolerated. Several molecules with high polar surface area were also indentified as potent CB1 receptor antagonists. The in vivo proof of principle for weight loss is exemplified with a lead compound from this series. (C) 2010 Elsevier Ltd. All rights reserved.